Perbaikan dan Perawatan Silinder Hidrolik Bucket Backhoe New Holland B80b di PT Altrak 1978 - Irawan Ardiansyah; Sunaryo; Indra Hasan (Journal of Management and Industrial Engineering (JMIE), 2024)
Heavy equipment in particular is one of the supporting tools for mining or industry which is very important in the production process. During the excavation process, the Rear attachment, especially the actuator, namely the hydraulic cylinder, works continuously during the process. This will of course cause problems that cannot be avoided. However, problems that occur can be minimized with preventive measures and maintenance. It is hoped that the existence of preventive and maintenance steps will make it easier for mechanics to carry out preventive and maintenance steps on hydraulic cylinder components. The main method used in this report is comprehension. The data obtained is taken from an understanding that refers to the problem. Second, the observation method. This method is taken when carrying out work practices. The final method is interviews, by asking questions about problems that often occur to employees who are experienced in their field. Common problems in hydraulic cylinders such as leaks and contamination can be minimized with preventive and maintenance measures, starting from choosing the right oil, preventive maintenance, and operating the unit correctly. If preventive and maintenance steps are carried out properly, repairs to components will of course be easier.